1998
DOI: 10.1161/01.atv.18.12.1844
|View full text |Cite
|
Sign up to set email alerts
|

Tibolone Prevents Atherosclerotic Lesion Formation in Cholesterol-Fed, Ovariectomized Rabbits

Abstract: Abstract-Tibolone (Org OD14), a synthetic steroid with estrogenic and progestogenic/androgenic properties, is clinically effective for the treatment of climacteric symptoms and the prevention and treatment of osteoporosis in postmenopausal women. The effect on atherogenesis, however, is not known. In the current study, we investigated the effect of tibolone in comparison with that of estradiol and norethisterone acetate on atherogenesis in 140 ovariectomized New Zealand White rabbits that had been induced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 68 publications
(73 reference statements)
3
16
0
Order By: Relevance
“…27 Indeed, tibolone prevented cholesterol accumulation and fatty streak formation in the aorta and the impairment of endothelium-dependent smooth muscle relaxation of the aorta, and these beneficial effects were plasma lipid independent. 8 Also, there is no clinical evidence indicating that tibolone increases CHD rates. 7 Tibolone has effects similar to those of probucol regarding the antioxidant effect and the HDL cholesterol-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Indeed, tibolone prevented cholesterol accumulation and fatty streak formation in the aorta and the impairment of endothelium-dependent smooth muscle relaxation of the aorta, and these beneficial effects were plasma lipid independent. 8 Also, there is no clinical evidence indicating that tibolone increases CHD rates. 7 Tibolone has effects similar to those of probucol regarding the antioxidant effect and the HDL cholesterol-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nonetheless, its antiatherosclerotic effects have been questioned because of consistent reductions in the levels of HDL cholesterol, which has antiatherosclerotic properties. However, recent animal studies have demonstrated that the use of tibolone results in significantly less atherosclerosis than does use of placebo 8 or, at least, that use of tibolone compared with control results in no increase in coronary atherosclerosis, 9 despite a marked reduction of HDL choles-terol levels. Overall, tibolone has complex effects on lipids, some that might be expected to improve vasomotor function and others that might worsen vasomotor function.…”
mentioning
confidence: 99%
“…Tibolone protects ovariectomized and cholesterol-fed rabbits from atherosclerosis (Zandberg et al 1998). Specifically, in the arterial wall tibolone almost completely prevented atherogenesis.…”
Section: Tibolone and Atherosclerosismentioning
confidence: 89%
“…It reduced the accumulation of cholesterol, fatty streak formation, impairment of endothelium-dependent response, and advanced lesion formation after endothelial damage. Importantly, a substantial part of these beneficial effects were plasma lipid independent (Zandberg et al 1998). However, the value of these potential antiatherosclerotic effects have been questioned in view of the fact that tibolone reduces HDL cholesterol levels by about 20 to 30%.…”
Section: Tibolone and Atherosclerosismentioning
confidence: 99%
“…32 Furthermore in an atherosclerotic rabbit model tibolone significantly reduced the development of new atherosclerotic plaque. 33 It has androgenic effects on plasma lipids especially in reducing HDL. This study shows tibolone has no differential effect on HDL-cholesterol uptake and transfer as HDL and apoA1 levels were reduced in parallel.…”
Section: Discussionmentioning
confidence: 99%